Effect of preadmission beta-blockade on mortality in multiple trauma. Issue 6 (23rd June 2018) - Eriksson, M; von Oelreich, E; Brattström, O; Eriksson, J; Larsson, E; Oldner, A
Abstract: Background: High levels of circulating catecholamines after multiple trauma have been associated with increased morbidity and mortality. Beta-adrenergic receptor antagonist (beta-blocker) therapy has emerged as a potential treatment option, but the effect of preinjury beta-blockade on trauma-induced mortality is unclear. The aim of this study was to assess whether preinjury beta-blocker therapy is associated with reduced mortality after multiple trauma. Methods: Severely injured patients, aged at least 50 years, admitted to a level one trauma centre over a 10-year interval were linked to national and local registries of co-morbidities, prescription drug use and level of education. The association between preinjury beta-blocker use and 30-day mortality was explored using logistic regression analysis. Results: Some 1376 patients were included; 338 (24·6 per cent) were receiving beta-blockers at the time of trauma. Beta-blocker users had an increased crude 30-day mortality rate compared with that for non-users: 32·8 versus 19·7 per cent respectively ( P < 0·001). After adjustment for baseline imbalances and injury-related factors, there was no association between preinjury beta-blocker use and mortality (OR 1·09, 95 per cent c.i. 0·70 to 1·70). Separate analyses of individuals with or without severe head injury did not significantly change this association. There was no significant difference in the rate of shock between beta-blocker users and non-users. Conclusion: Pretrauma beta-blockade is not associated with 30-day mortality beyond the effects of age, co-morbidity and injury severity. Graphical Abstract: In this study including 1376 severely injured patients, the authors analysed whether pretraumatic β-blockade would be protective. After adjustment for baseline imbalances and injury-related factors, there was no association between pretraumatic β-blocker use and mortality. Separate analyses of patients with or without severe head injury did not change this association significantly. No mortality reduction seen